Total Syntheses of (+)‐Valiolamine and (–)‐1‐epi‐Valiolamine from Naturally Abundant (–)‐Shikimic Acid. Issue 28 (15th August 2013) - Quan, Na; Nie, Liang‐Deng; Zhu, Rui‐Heng; Shi, Xiao‐Xin; Ding, Wei; Lu, Xia
Abstract: Total syntheses of (+)‐valiolamine (1 ) and (–)‐1‐ epi ‐valiolamine (2 ) from the naturally abundant (–)‐shikimic acid are described. Ethyl 3‐ epi ‐5‐ O ‐methylsulfonyl‐shikimate (3 ), as the key common intermediate, was first synthesized in five steps in 74 % overall yield, and then converted into the targets1 and2 in seven steps in 48 and 41 % overall yield, respectively. Abstract : Total syntheses of (+)‐valiolamine (1 ) and (–)‐1‐ epi ‐valiolamine (2 ) from (–)‐shikimic acid are described. Ethyl 3‐ epi ‐5‐ O ‐methylsulfonyl‐shikimate (3 ), as the key common intermediate, was first synthesized in five steps (74 % yield) and then converted into the targets in seven steps in 48 and 41 % overall yield, respectively.